Fabrication of proton exchange membrane for non-humidified fuel cells based on polyimide Matrimid® and hydrophobic protic ionic liquid - Rogalsky, Sergiy P.; Tarasyuk, Oksana P.; Cherniavska, Tetiana V.; Babkina, Natalia V.; Dzhuzha, Oleg V.; Shybyryn, Olena V.; Makhno, Stanislav M. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
New proton exchange membrane based on polyimide Matrimid® (PI) and hydrophobic protic ionic liquid, 1-methylimidazolium bis(trifluoromethylsulfonyl)imide (MIM-TFSI), has been prepared by casting from methylene chloride/dimethylformamide solution. Infrared analysis revealed physicochemical interactions between 1-methylimidazolium cations and imide groups of PI. The results of mechanical testing indicate significantly reduced tensile strength of PI/MIM-TFSI composite membrane compared to neat polymer. Moreover, the dynamical mechanical analysis results revealed sharp drop in storage modulus (E´) of the polymer film above 60 °C. To improve the elastic properties of the membrane, PI was successively cross-linked with polyetheramine Jeffamine® D-2000 (10 mol. %) in methylene chloride/dimethylformamide solution, as well as in solid film at 100 °C. This approach allowed to prepare PI/Jeffamine/MIM-TFSI (70 wt. %) composite film which has an acceptable E' value of 210 MPa at 140 °C. According to thermal gravimetric analysis data, PI/Jeffamine/MIM-TFSI composite has a thermal degradation point (i.e. 5 % weight loss) of 286 °C. The ionic conductivity of PI/Jeffamine/MIM-TFSI composite membrane is around 10–4 S/cm at room temperature and reaches the minimal level of 10–3 S/cm, required for fuel cell applications, above 100 °C. Overall, the results of this study indicate that the cross-linking of polyimide Matrimid with flexible polyetheramine Jeffamine is an efficient approach for preparing dense composite membrane with high content of the protic ionic liquid. Such polymer-electrolyte membrane has the reasonable combination of good stiffness, thermal stability, and ionic conductivity and therefore is a promising candidate for use in fuel cells operating at elevated temperatures in water-free conditions.